Relatar a través del trauma del perpetrador. Memoria y representación en The Act of Killing de Joshua Oppenheimer - Álvaro MARTÍN SANZ (Fonseca, Journal of Communication, 2023)
Faced with the fear of the surviving victims to denounce the crimes that took place in the Indonesian genocide, the filmmaker Joshua Oppenheimer elaborates in The Act of Killing a non-fiction device centred on the figure of the perpetrators as narrators of the story. This daring and unusual approach involves a constant tension of forces between the filmmaker's authorial voice and that of Anwar Congo, the former perpetrator who is the protagonist of the film